2019
DOI: 10.3389/fpsyg.2019.02832
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Implicit Attitudes Toward Students From Different Social Groups: A Meta-Analysis

Abstract: Teachers' attitudes toward their students have been associated with differential teachers' expectations and, in turn, with students' educational pathways. Theories of social cognition can explain the link between attitudes and behavior. In this regard, the distinction between implicit and explicit attitudes is worth to be considered, whereby implicit attitudes are automatically activated when the attitude object is present and guide automatic behavior. In contrast, explicit attitudes infer deliberation and ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 123 publications
1
16
0
Order By: Relevance
“…At the same time, however, findings indicate that although young adults had both aspirations and resilience, they reported vulnerabilities in other areas such as financial difficulties and mental health challenges and there was an obvious absence of teachers making a positive impact. Our finding of teachers' lack of influence may be due to implicit attitudes and consistent with teachers reproducing social inequalities (Delay, 2020;Pit-Ten & Glock, 2019). Future research should explore in greater depth what protective factors contribute to resilience among this population and how factors such as type and length of maltreatment impact the ability to develop resilience.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…At the same time, however, findings indicate that although young adults had both aspirations and resilience, they reported vulnerabilities in other areas such as financial difficulties and mental health challenges and there was an obvious absence of teachers making a positive impact. Our finding of teachers' lack of influence may be due to implicit attitudes and consistent with teachers reproducing social inequalities (Delay, 2020;Pit-Ten & Glock, 2019). Future research should explore in greater depth what protective factors contribute to resilience among this population and how factors such as type and length of maltreatment impact the ability to develop resilience.…”
Section: Discussionsupporting
confidence: 64%
“…Teachers may also have a limiting or negative impact on students. A meta-analysis of 34 studies found that teachers hold negative implicit attitudes towards marginalized students (Pit-Ten & Glock, 2019) and attitudes about a social group are expressed daily in exchanges with students. A recent study in Switzerland found teachers' classroom discourse influences the choices of students who have been tracked into vocational education (Delay, 2020).…”
Section: Teachers and Post-secondary Educationmentioning
confidence: 99%
“…More specifically, inservice teachers' implicit attitudes were more negative than those of preservice teachers, but both groups held negative implicit attitudes. However, one recent review (Denessen et al, 2021) and a meta-analysis (Pit-ten Cate & Glock, 2019) did not find differences between preservice and inservice teachers but generally reported negative implicit attitudes. This does not seem to stem entirely from a strong negative evaluation of ethnic minority students but mainly results from more positive implicit attitudes toward ethnic majority students (Glock & Karbach, 2015).…”
Section: Attitudesmentioning
confidence: 98%
“…Inclusive education (IE) is the idea that education is a basic human right for all students, following the principles of social justice [15]. The World Declaration on Education for All (EFA) defined general principles of IE as providing universal access to schools for everyone and promote equity, being proactive and predicting barriers in access to education and identifying recourses to eliminate such barriers [16].…”
Section: Response To Interventionmentioning
confidence: 99%